Managing Asia: A 21st Century “Chingbirok”? Opportunities in Trade Balanced Against Risk Factors In East, South, and Southeast Asian Security - Jones, David A. (New Dynamics in Asia, 2020)
Asia requires management in areas that interface, including manufacturing and assembly of goods, quality control, transportation of raw materials, delivery of finished products to markets, protecting intellectual property, providing services. Some management should be domestic, subject to different traditions and values within each country. Domestic Asian management, even pan-Asian management, is not working optimally. A “Chingbirok” or “Book of Corrections” seems required. Implicitly, this is an invitation for foreign partners to join into this conversation, because the welfare of all nations concerned depends upon effective and efficient management of Asia, especially the economies of populous Asian countries themselves. Actual and rhetorical belligerence should subside, Sino-American and Sino-European investment should be optimised, freedom of maritime navigation maintained through deterrence strategies. This paper will outline essentially an Anglo-American plan to secure a competitive maritime corridor across the “Near” Seas from Japan through the Suez Canal to the Mediterranean, an overland railway and highway across the Russian Federation, plus an alternative seaway across the Arctic Ocean, rendered navigable by global warming. America’s primary responsibility may focus on protecting Taiwan plus East Asian countries, with Britain’s to concentrate on safeguarding the Indian subcontinent and Malaysia as its former colonies. Functionally, the United Kingdom and United States should assume a proactive role in providing investment and oversight across China’s “New Silk Road” to ensure harmony and deter the outbreak of hostilities within Eurasia, exerting muscular intervention in cooperation with their Asian Allies as required. Concrete objectives should be to maintain self-governance of Taiwan and all Asian states, unfettered South China Sea navigation, preservation of Western technology from Chinese plunder or coerced acquisition, together with an opportunity for a rising Asian middle class to purchase Western goods without restriction, each a component of America’s Free and Open Indo-Pacific (FOIP) Strategy articulated by President Donald J. Trump.